2020
DOI: 10.1002/acr.23835
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Upper Limb Joint Surgery Among Rheumatoid Arthritis Patients: An Interrupted Time‐Series Analysis Using Danish Health Care Registers

Abstract: Objective Joint replacement surgery is a proxy of severe joint damage in rheumatoid arthritis (RA). The aim of this study was to assess the impact of the introduction of biologic disease‐modifying antirheumatic drugs (bDMARDs) on the incidence rate (IR) of upper limb joint replacements among newly diagnosed RA patients. Methods Using the Danish National Patient Register, patients with incident RA from 1996–2012 were identified. Each patient was matched on age, sex, and municipality, with up to 10 general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…With this in mind, the management of antirheumatic medications that could potentially increase this risk is an important decision that many physicians and patients face at some point during the course of the rheumatic disease. Since the introduction of bDMARD therapies in the early 2000s, surgical interventions have fortunately decreased, not only in Germany but also in many other countries [49][50][51][52][53]. Nevertheless, surgical interventions are still more frequent in patients with inflammatory rheumatic diseases than in the healthy population [54].…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, the management of antirheumatic medications that could potentially increase this risk is an important decision that many physicians and patients face at some point during the course of the rheumatic disease. Since the introduction of bDMARD therapies in the early 2000s, surgical interventions have fortunately decreased, not only in Germany but also in many other countries [49][50][51][52][53]. Nevertheless, surgical interventions are still more frequent in patients with inflammatory rheumatic diseases than in the healthy population [54].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the prevalence among cases of elbow, shoulder, and ankle replacement surgeries decreased by 50%, 18%, and 38%, respectively. Cordtz et al [ 2 ] evaluated the incidence of joint replacement before (1996–2001) and after (2003–2012) the introduction of bDMARDs in patients diagnosed with RA in Denmark between 1996 and 2012. They reported that the incidence of joint replacement in RA patients was stable from 1996 to 2001 but started to decrease from 2003, suggesting an association between the introduction of bDMARDs and a lower need for joint replacements among patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“… 3 While use of both conventional and targeted DMARDs has increased, and the rates of upper extremity and small joint surgery have decreased, the rates of total hip (THA) and total knee arthroplasty (TKA) have not. 2 4 In one recent study using propensity matching and adjusting for disease activity, tumour necrosis factor inhibitor (TNFi) use was not associated with decreased rates of THA or TKA. 5 Therefore, patients with RA continue to undergo THA and TKA, despite high utilisation of targeted and csDMARDs and glucocorticoids, which most patients are taking at the time of surgery.…”
Section: Introductionmentioning
confidence: 99%